Promoting mental health awareness among teachers in Malaysia: Assessing the role of sustainable development goals in enhancing well-being - Normazhazlin, Alzahari; Yarina, Ahmad; Noraine, Bahari (The Global Goal, 2025)
Objective: Teachers in Malaysia face significant challenges related to stress, anxiety, and depression, which negatively impact their mental well-being and professional effectiveness. Despite growing awareness of mental health issues, teachers often lack adequate support and resources to manage these pressures. Aligned with Sustainable Development Goal (SDG) 3, which promotes good health and well-being for all, this study emphasizes the importance of mental health awareness in improving teachers’ overall quality of life.